STAT4 Deficiency Fails To Induce Lung Th2 or Th17 Immunity following Primary or Secondary Respiratory Syncytial Virus (RSV) Challenge but Enhances the Lung RSV-Specific CD8(+) T Cell Immune Response to Secondary Challenge - Dulek, Daniel E. (American Society for Microbiology, 2014)
Immune-mediated lung injury is a hallmark of lower respiratory tract illness caused by respiratory syncytial virus (RSV). STAT4 plays a critical role in CD4(+) Th1 lineage differentiation and gamma interferon (IFN-γ) protein expression by CD4(+) T cells. As CD4(+) Th1 differentiation is associated with negative regulation of CD4(+) Th2 and Th17 differentiation, we hypothesized that RSV infection of STAT4(−/−) mice would result in enhanced lung Th2 and Th17 inflammation and impaired lung Th1 inflammation compared to wild-type (WT) mice. We performed primary and secondary RSV challenges in WT and STAT4(−/−) mice and used STAT1(−/−) mice as a positive control for the development of RSV-specific lung Th2 and Th17 inflammation during primary challenge. Primary RSV challenge of STAT4(−/−) mice resulted in decreased T-bet and IFN-γ expression levels in CD4(+) T cells compared to those of WT mice. Lung Th2 and Th17 inflammation did not develop in primary RSV-challenged STAT4(−/−) mice. Decreased IFN-γ expression by NK cells, CD4(+) T cells, and CD8(+) T cells was associated with attenuated weight loss and enhanced viral clearance with primary challenge in STAT4(−/−) mice compared to WT mice. Following secondary challenge, WT and STAT4(−/−) mice also did not develop lung Th2 or Th17 inflammation. In contrast to primary challenge, secondary RSV challenge of STAT4(−/−) mice resulted in enhanced weight loss, an increased lung IFN-γ expression level, and an increased lung RSV-specific CD8(+) T cell response compared to those of WT mice. These data demonstrate that STAT4 regulates the RSV-specific CD8(+) T cell response to secondary infection but does not independently regulate lung Th2 or Th17 immune responses to RSV challenge. IMPORTANCE STAT4 is a protein critical for both innate and adaptive immune responses to viral infection. Our results show that STAT4 regulates the immune response to primary and secondary challenge with RSV but does not restrain RSV-induced lung Th2 or Th17 immune responses. These findings suggest that STAT4 expression may influence lung immunity and severity of illness following primary and secondary RSV infections.